PRACTICAL MODELS OF COOPERATION BETWEEN MEDIA AND CHARITABLE ORGANIZATIONS - Dudka, Natalia (European Journal of Interdisciplinary Issues, 2025)
The article focuses on analyzing practical models of cooperation between media and charitable organizations in the context of building their public presence and ensuring transparency of operations. The aim of the study is to explore how charitable organizations apply communication strategies and channels in the modern media environment, taking into account regulatory requirements for openness and accountability. The study employed general scientific methods of cognition: analysis, synthesis, comparison, generalization, and a systems approach. The findings show that charitable organizations in Ukraine are actively adopting an integrated cross-channel approach to shaping their public presence. In particular, they utilize social media platforms (Facebook, Instagram, TikTok), official websites, email newsletters, television, external media, and personalized channels through collaboration with influencers. This strategy enables them to reach a broad audience, establish emotional connections with the public, share information about their activities, and attract necessary resources. Special attention is given to issues of public reporting, as required by current legislation: informing donors about the targeted use of donations, ensuring financial openness and transparency. This necessitates transforming communication strategies into tools of accountability that enhance public trust in the charitable sector. The study examines promising directions for improving communication strategies, with a focus on the implementation of digital technologies, personalized content, infographics, result visualization, and in-depth analytics. The importance of creating technically accessible solutions for publishing public reports on organizations’ official resources is emphasized. As the study reveals, the improvement of strategies should be based on systematic analysis, adaptability to target audiences, and the application of effective cross-sector management practices.